Stuttering in Parkinson's disease after deep brain stimulation: A note on dystonia and low-frequency stimulation. (April 2018) - Mendonça, Marcelo D.; Barbosa, Raquel; Seromenho-Santos, Alexandra; Reizinho, Carla; Bugalho, Paulo; ,
Highlights: Stuttering can be a side effect of Subthalamic Deep Brain Stimulation. Stuttering was stimulation dependent. Stuttering developed while limb dystonia improves with Deep Brain Stimulation. Abstract: Stuttering, a speech fluency disorder, is a rare complication of Deep Brain Stimulation (DBS) in Parkinson's Disease (PD). We report a 61 years-old patient with PD, afflicted by severe On and Off dystonia, treated with Subthalamic Nucleus DBS that developed post-DBS stuttering while on 130 Hz stimulation. Stuttering reduction was noted when frequency was changed to 80 Hz, but the previously observed dystonia improvement was lost. There are no reports in literature on patients developing stuttering with low-frequency stimulation. We question if low-frequency stimulation could have a role for managing PD's post-DBS stuttering, and notice that stuttering improvement was associated with dystonia worsening suggesting that they are distinct phenomena.